Exploring Malawi’s Export Potential - International Trade Centre (United Nations, 2018)
Regional integration is the key to Malawi’s trade success, according to a new ITC report that uncovers the country’s greatest untapped export potential in agro-processing. This report is a roadmap for Malawian exporters and policymakers to identify higher value-added products and markets with growth potential, as well as giving guidance to realize these opportunities and overcoming production challenges.